Mast cells partly contribute to allergic enteritis development: Findings in two different mast cell-deficient mice - Blanco Pérez, Frank (2021)
Allergic enteritis (AE) is a gastrointestinal form of food allergy. The presence of mast cells and granulocytes has been detected in the inflamed tissues in AE. In this study, we aimed to elucidate the role of mast cells in AE development using two mast cell-deficient mouse strains: KIT(W-sh/W-sh) bearing the W-sash (W(sh)) inversion mutation and Cpa3Cre/+, which lack mast cells due to Cre-mediated mast cell eradication, were used in an AE experimental model. The development of clinical symptoms (e.g. drop in body temperature and weight loss) were abolished in both strains, whereas inflammatory levels of AE (e.g. villous atrophy, edema, and granulocyte accumulation) were reduced mainly in KITW-sh/W-sh mice. FACS analysis of the KITW-sh/W-sh intestinal lamina propria, showed a reduction in the eosinophil (CD45+CD11b+SiglecF+cells) and neutrophil (CD45+CD11b+SiglecF−Ly6G+ cells) accumulation. Cpa3Cre/+ mice showed reduced eosinophil (CD45+CD11b+SiglecF+cells) accumulation, but neutrophil (CD45+CD11b+SiglecF−Ly6G+ cells) accumulation was retained at AE sites. The concentrations of CC chemokine ligand 1 (CCL1), a known CC chemokine receptor 8 ligand leading to eosinophil recruitment, was reduced in intestinal homogenates of both mast cell-deficient mouse strains. These results suggest that mast cells play a role in AE development in part by expressing CCL1 and contributing to eosinophil accumulation at AE. This study offers implications for establishing AE treatments that target infiltrating leucocytes in AE tissues.